2017
DOI: 10.1037/str0000038
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of challenge and hindrance appraisals of working conditions for employees’ health.

Abstract: Psychosocial risk assessments are frequently applied with an a priori classification of favorable and unfavorable working conditions. However, such classifications contradict transactional stress theory and the results of research that found the effects of work stressors on wellbeing to be dependent on boundary conditions. The challenge/hindrance framework assumes that the effects of stressors on wellbeing depend on their individual appraisal as either challenge (stressors associated with personal gain) or hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
(50 reference statements)
1
39
1
3
Order By: Relevance
“…Similar single item measures for stressor appraisal were used by Webster et al (2011). We chose however, a slightly different wording (Gerich 2016) with a stronger emphasis on the differentiation between challenge and hindrance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar single item measures for stressor appraisal were used by Webster et al (2011). We chose however, a slightly different wording (Gerich 2016) with a stronger emphasis on the differentiation between challenge and hindrance.…”
Section: Methodsmentioning
confidence: 99%
“…The different results may be attributable to a difference in the measurement of challenge appraisal. Whereas Webster et al's (2011) question on challenge appraisal expressed an attenuation of hindrance (although "potentially stressful, something you think you can overcome"), the notion of personal gain was more pronounced in Gerich's (2016) question of whether a working condition was perceived as a "beneficial opportunity or challenge". Searle and Auton (2015) applied multiple item measures of challenge and hindrance appraisal and confirmed indirect effects of opposite direction for stressors via challenge and hindrance appraisal on work-related affective states.…”
Section: The Challenge-hindrance Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…Although several mediators of the effects of challenge–hindrance stressors on some outcomes have been studied (e.g., self‐efficacy, Webster, Beehr, & Christiansen, ) , a recurring question is whether appraisal mediates the relationship between stressors and the primary stress outcome of strain. One study of 631 Austrian employees focused on the strains of burnout, health, and health symptoms and found that employees' hindrance appraisals generally mediated the effects of working demands (e.g., time pressure, scope of action, qualitative demands, and responsibility), whereas for challenge appraisals there was less evidence for mediation (Gerich, ). Another study found that both challenge and hindrance appraisals tended to mediate the relationships between stressors with strains, job satisfaction, and turnover intentions (e.g., Webster et al, ).…”
Section: Causal Mechanismsmentioning
confidence: 99%